Prevalence, predictors and outcomes of potential drug-drug interactions in left ventricular failure: considerable factors for quality use of medicines - Inamul Haq; Mohammad Ismail; Fahadullah Khan; Qasim Khan; Zahid Ali; Sidra Noor (Universidade de São Paulo, 2020)
Hospitalized patients with left ventricular failure (LVF) are at high risk for potential drug-drug interactions (pDDIs) and its related adverse effects owing to multiple risk factors such as old age, comorbidities and polypharmacy. This cross-sectional study conducted in two tertiary care hospitals aim to identify frequency, levels and predictors of pDDIs in LVF patients. Data about patients' demographic, hospital stay, medication therapy, sign/symptoms and laboratory test results were collected for 385 patients with LVF. Micromedex Drug-Reax® was used to screen patients' medication profiles for pDDIs. Overall prevalence and severity-wise prevalence of pDDIs were identified. Chi-square test was performed for comparative analysis of various variables. Logistic regression was applied to determine the odds-ratios (OR) for predictors of pDDIs. The prevalence of pDDIs was 96.4% (n=371). Overall 335 drug-interacting pairs were detected, which were presented in a total of 2870 pDDIs. Majority of pDDIs were of major- (48.9%) and moderate-severity (47.5%). Logistic regression analysis shows significant association of >6 all types of pDDIs with >12 drugs as compared with <8 drugs (OR=16.5; p=<0.001). Likewise, there was a significant association of >4 major-pDDIs with men as compared with female (OR=1.9; p=0.007) and >12 drugs as compared with <8 drugs (OR=10.9; p=<0.001). Hypotension (n=57), impaired renal function (23) and increased blood pressure (22) were the most frequent adverse outcomes associated with pDDIs. This study shows high prevalence of pDDIs in LVF patients. Majority of pDDIs were of major- and moderate-severity. Male patients and those prescribed greater number of medicines were more exposed to major-pDDIs.